METHODS OF CREATING A SYSTEM OF GRAPHIC DESIGN ASSIGNMENTS FROM DRAWING - Rustamov Akhtam Mukhtarovich (Galaxy International Interdisciplinary Research Journal, 2022)
In the theory of graphic assignments, such terms as "assignment", "teaching assignment", "knowledge assignment", "creative assignment", "practical assignment", "ualual assignment"," problem "are also used side by side with such terms as" exercise"," independent work". To determine the essence of the" creative graphic task", to give it a didactic, methodical definition, we first give a description of the definitions given to the concept of teaching assignment in psychology, didactics, methodology.